2021
DOI: 10.1128/iai.00258-21
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling Reveals CD73 and Age-Driven Changes in Neutrophil Responses against Streptococcus pneumoniae

Abstract: Neutrophils are required for host resistance against Streptococcus pneumoniae but their function declines with age. We previously found that CD73, an enzyme required for antimicrobial activity, is down-regulated in neutrophils from aged mice. This study explored transcriptional changes in neutrophils induced by S. pneumoniae to identify pathways controlled by CD73 and dysregulated with age. Pure bone marrow-derived neutrophils isolated from wild type (WT) young, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…We previously found that scavenging/ detoxifying ROS completely abrogates the ability of PMNs to kill S. pneumoniae [12]. To determine if mitochondrial ROS were important for the antimicrobial function of PMNs, we treated PMNs with MitoTEMPO and measured the ability of PMNs to kill S. pneumoniae TIGR4 strain using an established opsonophagocytic (OPH) killing assay [2, 12, 3234, 49]. We found that treatment with MitoTEMPO lead to a complete abrogation of bacterial killing by PMNs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously found that scavenging/ detoxifying ROS completely abrogates the ability of PMNs to kill S. pneumoniae [12]. To determine if mitochondrial ROS were important for the antimicrobial function of PMNs, we treated PMNs with MitoTEMPO and measured the ability of PMNs to kill S. pneumoniae TIGR4 strain using an established opsonophagocytic (OPH) killing assay [2, 12, 3234, 49]. We found that treatment with MitoTEMPO lead to a complete abrogation of bacterial killing by PMNs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Pathways that regulate MitROS production by PMNs have not been explored. Extracellular adenosine (EAD) is a key regulator of PMN responses during pneumococcal infection [2, 12, 3234]. EAD is produced in the extracellular environment as a breakdown product of ATP released from damage cells where two extracellular enzymes CD39 and CD73 sequentially de-phosphorylate ATP to EAD [35].…”
Section: Introductionmentioning
confidence: 99%
“…However, traditional detection methods for P. aeruginosa may cause false positives or missed positives and are considerably time-consuming. Automated systems such as VITEK 2, which walkway system that works on the principle of photometry, promise shorter turnaround times to detect P. aeruginosa , but these systems have a low rate of accuracy in the identification ( Torrecillas et al, 2020 ; Bhalla et al, 2021 ; Miranda-Ulloa et al, 2021 ; Pintado-Berninches et al, 2021 ; Viedma et al, 2021 ). Immunological approaches use the highly specific binding between antigens and antibodies and facilitate qualitative or quantitative detection that is based on specific reactions resulted from antigen antibody binding ( Rainbow et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Immunological approaches use the highly specific binding between antigens and antibodies and facilitate qualitative or quantitative detection that is based on specific reactions resulted from antigen antibody binding ( Rainbow et al, 2020 ). High-sensitivity detection has been reached by modern immunoassay approaches, but their relatively tedious procedures have limited further development ( Bhalla et al, 2021 ; Miranda-Ulloa et al, 2021 ; Viedma et al, 2021 ). In addition, greatest drawback of immunofluorescence methods is a low signal-to-noise ratio, which may lower its detection specificity ( Pintado-Berninches et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, young patients versus elderly patients had more alveolar macrophages [ 146 ]. The activation of c-Jun N-terminal kinase/activator protein-1 (JNK/AP-1), one of the MAPK signaling pathways, was significantly upregulated in response to S. pneumoniae infection in PMNs from old mice compared to young controls, and its pharmacological inhibition reversed the defect in pneumococcal killing by PMNs, indicating that this pathway can potentially be targeted to reverse the age-related dysregulation of PMN responses [ 147 ]. Lower IL-10 production was associated with higher levels of chemokine ligands CXCL9, CXCL12, CCL3, CCL4, CCL5, CCL11 and CCL17 in infected old mice, suggesting a defect in anti-inflammatory cytokine production by immune cells in the lung [ 145 ].…”
Section: Immune Response To Infection In Agingmentioning
confidence: 99%